2018
DOI: 10.22159/ajpcr.2018.v11i9.27667
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Gastric Gas Emptying on the Residual Gastric Volume in Mechanically-Ventilated Intensive Care Unit Patients Fed Through Nasogastric Tubes: A Randomized, Single-Blind, Clinical Trial

Abstract: Objective: Increased gastric residual volume is a complication of enteral nutrition intolerance that leads to gastrointestinal complications such as nausea, vomiting, and aspiration pneumonia. The present study was conducted to determine the effect of gastric gas emptying on the residual gastric volume in mechanically-ventilated patients fed through nasogastric tubes.Methods: This randomized, single-blind, clinical trial was conducted on two groups of patients in the intensive care unit (ICU) of Kamyab Hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
1
0
1
Order By: Relevance
“…penelitiannya menciptakan stimulasi dan sedikit tekanan pada daerah epigastrium dan dengan demikian mendorong gerakan dari sistem pencernaan dan menyebabkan pengosongan gas lambung, sehingga mencegah muntah, distensi abdomen pada pasien, mengosongkan perut dan mengurangi sisa volume lambung pada pasien (Mohammadpour A, 2018). SIMPULAN Penerapan aplikasi jurnal pijat perut yang dilakukan pada pasien kritis yang terpasang NGT (Nasogastric Tube) dengan jumlah volume residu lambung berlebih, efektif mengurangi atau menurunkan jumlah volume residu lambung dan bisa diaplikasikan langsung pada pasien-pasien kritis.…”
Section: Saranunclassified
“…penelitiannya menciptakan stimulasi dan sedikit tekanan pada daerah epigastrium dan dengan demikian mendorong gerakan dari sistem pencernaan dan menyebabkan pengosongan gas lambung, sehingga mencegah muntah, distensi abdomen pada pasien, mengosongkan perut dan mengurangi sisa volume lambung pada pasien (Mohammadpour A, 2018). SIMPULAN Penerapan aplikasi jurnal pijat perut yang dilakukan pada pasien kritis yang terpasang NGT (Nasogastric Tube) dengan jumlah volume residu lambung berlebih, efektif mengurangi atau menurunkan jumlah volume residu lambung dan bisa diaplikasikan langsung pada pasien-pasien kritis.…”
Section: Saranunclassified
“…In addition, nutritional support considered as fundamental aspect of a standard caring of critical ill patients in intensive care units (ICUs) [1,2]. It was reported that more than 40%to 50% of critically ill patients suffer from malnutrition [3]. In addition, through their initial stay in the ICU they lose about 5-10% skeletal muscle mass weekly [4].…”
Section: Introductionmentioning
confidence: 99%